An Inhibitive Enzyme Assay to Detect Mercury and Zinc Using Protease from Coriandrum sativum - Gunasekaran Baskaran; Noor Azlina Masdor; Mohd Arif Syed; Mohd Yunus Shukor (The Scientific World Journal)
Heavy metals pollution has become a great threat to the world. Since instrumental methods are expensive and need skilled technician, a simple and fast method is needed to determine the presence of heavy metals in the environment. In this study, an inhibitive enzyme assay for heavy metals has been developed using crude proteases from Coriandrum sativum. In this assay, casein was used as a substrate and Coomassie dye was used to denote the completion of casein hydrolysis. In the absence of inhibitors, casein was hydrolysed and the solution became brown, while in the presence of metal ions such as Hg2+ and Zn2+, the hydrolysis of casein was inhibited and the solution remained blue. Both Hg2+ and Zn2+ exhibited one-phase binding curve with IC50 values of 3.217 mg/L and 0.727 mg/L, respectively. The limits of detection (LOD) and limits of quantitation (LOQ) for Hg were 0.241 and 0.802 mg/L, respectively, while the LOD and LOQ for Zn were 0.228 and 0.761 mg/L, respectively. The enzyme exhibited broad pH ranges for activity. The crude proteases extracted from Coriandrum sativum showed good potential for the development of a rapid, sensitive, and economic inhibitive assay for the biomonitoring of Hg2+ and Zn2+ in the aquatic environments.